2024
DOI: 10.1590/1519-6984.260355
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of lead in different organs of Ctenopharyngodon Idella (grass fish) and Tor putitora (Mahseer) fish

Abstract: Bioaccumulation of toxic heavy metals in the human body can give rise to adverse health effects, the severity of which depends upon their dosage and duration of exposure. In this study, yearlings of two different species of edible fish, i.e., Tor putitora (Mahseer) and Ctenopharyngodon Idella (grass carp), were exposed to different concentrations of lead nitrate in a controlled environment of aquarium for three different lengths of duration (14, 28, and 60 days). The bioaccumulation of lead in different organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Another plausible explanation for the lower concentration levels of the heavy metals in muscle tissues of fish compared to the other organs examined could be attributed to the fact that muscle tissue has low metal binding protein (metallothioneins). Zhang et al (2018) and Latif et al (2022) observed similar findings.…”
Section: Discussionsupporting
confidence: 66%
“…Another plausible explanation for the lower concentration levels of the heavy metals in muscle tissues of fish compared to the other organs examined could be attributed to the fact that muscle tissue has low metal binding protein (metallothioneins). Zhang et al (2018) and Latif et al (2022) observed similar findings.…”
Section: Discussionsupporting
confidence: 66%
“…This is of particular concern because of the large consumption of fish muscle worldwide. 16 The dose response risk analysis through the ingestion route to copper risk agents is 0.04 mg/kg×day and the slope factor (SF) value is 0.04 mg/kg×day and has a critical effect on liver damage (hepatic effect). 17 Cuprum can become toxic when it exceeds a certain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…These predatory fish can accumulate very high concentrations of methylmercury and are therefore of concern to human health. Mercury can also enter fish flesh through their gills or skin [ [70] , [71] , [72] ]. When fish breathe, they take in water that contains mercury and then it can be absorbed through the gills or skin.…”
Section: Types Of Contaminants In Fishmentioning
confidence: 99%